The relationship between mindful parenting, cognitive parental awareness, and the subjective well-being of adolescents - Ljubetić, Maja (Array, 2020)
The aim of this research is to explore the relationship between mindful parenting, cognitive parental awareness, and adolescents’ subjective well-being. The study included 101 families consisting of a mother, a father, and an adolescent child (N=303) aged 10 to 17, with a total of 69 female adolescents and 32 male adolescents. A general data questionnaire, mindful parenting questionnaire, and cognitive parental awareness questionnaire were administered to parents while adolescents completed a general data questionnaire, loneliness scale, life and family satisfaction scales, and general self-esteem scale. The results showed that male adolescents were more satisfied with life and had higher self-esteem than female adolescents. Measures of parenting were significantly related between mothers and fathers. The results also suggest that mindful parenting and cognitive parental awareness are significant correlates to the subjective well-being of adolescents when it comes to fathers, but not to mothers.